Shift work schedule and damage to nursing workers' health at Brazilian public hospital - Rosângela Marion da Silva; Juliana Tamiozzo; Eduardo Rodrigues Lauz; Flávia Camef Dorneles Lenz; Carolina Renz Pretto; Carmem Lúcia Colomé Beck; Alexa Pupiara Flores Coelho Centenaro; José Luís Guedes dos Santos (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to compare work-related damage between the day and night shifts of nursing workers in at a public hospital. Methods: a cross-sectional, and correlational study, conducted with 308 nursing workers from a Brazilian public hospital. Data collection took place from September 2017 to April 2018 using self-administered questionnaires that investigated socio-occupational variables and the effects of work (Work-Related Damage Assessment Scale). Analysis was descriptive and analytical with a 5% significance level. Results: during the day shift, the variables that most influenced nursing professionals' health were body pain, headache, back pain, legs pain, and sleep disorders. When comparing the shifts, it was identified that daytime influences the studied variables more than nighttime. Job tenure was correlated with psychological damage. Conclusions: the results showed a greater influence of the day shift on the health of professionals who work in a hospital environment. Job tenure influences psychological damage.